The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1088/1612-202x/ac4be8
|View full text |Cite
|
Sign up to set email alerts
|

Probing depth in diffuse reflectance spectroscopy of biotissues: a Monte Carlo study

Abstract: Diffuse reflectance spectroscopy (DRS) is an optical imaging modality based on extraction of tissue structural and functional information from back-reflectance spectra. In this paper we analyze the spectral dependence of DRS probing depth for different source-detector separations (SDSs) in the range of 1.5–7.0 mm by means of Monte Carlo simulations. The simulated spectra are employed to analyze the effect of the selected spectral range on the accuracy of oxygen saturation (StO2) reconstruction for different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Ultraviolet-visible diffuse reflectance spectra (UV-vis DRS) of the sample powders were collected on a UV-vis spectrophotometer (JASCO-750, Japan). The non-absorbing BaSO 4 was used as the reference material [53]. The sample powders were also analyzed by X-ray photoelectron spectroscopy (XPS, AXIS Ultra DLD, Japan) with a monochromatic Al Kα X-ray source for the examination of their surface state.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Ultraviolet-visible diffuse reflectance spectra (UV-vis DRS) of the sample powders were collected on a UV-vis spectrophotometer (JASCO-750, Japan). The non-absorbing BaSO 4 was used as the reference material [53]. The sample powders were also analyzed by X-ray photoelectron spectroscopy (XPS, AXIS Ultra DLD, Japan) with a monochromatic Al Kα X-ray source for the examination of their surface state.…”
Section: Materials Preparationmentioning
confidence: 99%
“…In general, there are two approaches that precede quantitative optical measurement of the living body: numerical calculations using Monte Carlo methods [5][6][7] and experimental approaches using phantoms [8][9][10][11] that have wavelength-dependent scattering and absorption characteristics unique to living tissue. Many studies on the detection ef ciency of SDS by Monte Carlo methods have been reported [12,13]. However, there are few reports on diffuse re ected light intensity detected in variable incident angles and SDS.…”
Section: Introductionmentioning
confidence: 99%
“…Optical imaging techniques [5,6] benefit from both non-invasiveness and high sensitivity to blood oxygenation owing to significant difference in absorption spectra of oxy-and deoxyhemoglobin in optical spectral range. Traditionally, blood oxygenation level is estimated with diffuse optical spectroscopy (DOS) [2,7,8] based on the registration of the spectra of the probing radiation passed through the biological tissue and the subsequent reconstruction of the medium absorption spectra from the measurement data [9,10]. This approach, however, provides with the estimation of blood oxygenation value averaged over a particular measurement volume within biological tissue.…”
Section: Introductionmentioning
confidence: 99%